A convergence analysis of a method of steepest descent and a two-step algorothm for nonlinear ill-posed problems. (December 2019) - Otmar, Scherzer
Abstract : In this paper a convergence analysis of a method of steepest descent and a two-step algorithm for solving nonlinear ill-posed problems is presented. Combined with an appropriate stopping criterion both methods turn out to be stable.